Extended distribution of Ficus costata Aiton (Moraceae) in Western Ghats, India. Issue 1 (9th March 2020) - Mohapatra, Abhipsa; Sudhakar, Jana Venkata; Janarthanam, Malapati Kuppuswamy
Abstract : Ficus costata Aiton, hitherto known only from Western Ghats of Kerala and Karnataka, and Nicobar Islands is recorded from Goa thus extending its distributional range. A detailed description, field photographs, anatomy and SEM images of cystoliths and distribution are provided.